The effect of public investment in road infrastructure on the Peruvian economic growth between the years 2000 and 2016 - Palacios Tovar, Carlos Arturo (2018)
The present research will show how public investment in road infrastructure influenced the gross domestic product (GDP) growth in Peru between the years 2000 and 2016. Likewise, it will determine which element generates competitiveness among the regions of the country.